Dampak Etika Komunikasi Publik Terhadap Citra Positif Pemerintah Provinsi Maluku - Sirait, Jimmy Purwata Mangasi; Tahitu, Amelia (KAMBOTI: Jurnal Sosial dan Humaniora, 2022)
The Impact of Public Communication Ethics on the Positive Image of the Maluku Provincial Government. This research uses quantitative methods, with data collection using field observations, questionnaires/questions. The purpose of this study was to determine the Impact of Public Communication Ethics on the Image of the Maluku Provincial Government. Through a purposive sampling technique, it was found that a sample of 42 respondents was spread across Nusaniwe and Sirimau Districts. The results of this study obtained communication ethics as measured through indicators of messages conveyed, messages received, messages rejected, as well as the attitude, character and nature of the recipient of the message, showing a significant influence. Based on the coefficient of determination test, it shows that 40.1% of the influence of public communication ethics has on the positive image of the Maluku Provincial government, while the remaining 59.9% is influenced by indicators and or other variables. Variable Y, namely the positive image of the Maluku provincial government with indicators namely ideas, beliefs, impressions and objects, is influenced by variable X, so that the result, the hypothesis is accepted.